Extract Ethanol of Poguntano in Alloxan Induced Diabetic Rats (Bangladesh Journal of Medical Science, 2018)
Back Ground: Diabetes mellitus is a group of metabolic disease with high blood glucose level above 150 mg/dL over a prolonged period. The elevated of blood glucose, free fatty acid and insulin resistance will cause the endothelial dysfunction, hemostasis disturbances that lead to micro and macrovascular complications. Poguntano (Picria fel-terrae Merr) from family Scrophulariaceae found in most part of Indonesia, has been used as traditional plant for treatment of diabetes.Objective: The purpose of this study was to investigate the effect of extract ethanol of Poguntano in alloxan induced diabetic rats.Method: Fifteen male Wistar rats with body weight of 150-200 gr were given intra peritoneal injection of 150 mg/kg Alloxan to induce diabetes. These were divided into three groups (control diabetic, group given insulin and group given Extract ethanol of Poguntano 200 mg/Kg body weight) and one control normal control. The duration of study was 4 weeks; blood glucose and Endothelin-1 were measured for all groups.Results : Extract ethanol of Poguntano 200 mg showed significant results (p